The 2020 Conference on Artificial Life 2020
DOI: 10.1162/isal_a_00243
|View full text |Cite
|
Sign up to set email alerts
|

Morphology dictates learnability in neural controllers

Abstract: Catastrophic forgetting continues to severely restrict the learnability of controllers suitable for multiple task environments. Efforts to combat catastrophic forgetting reported in the literature to date have focused on how control systems can be updated more rapidly, hastening their adjustment from good initial settings to new environments, or more circumspectly, suppressing their ability to overfit to any one environment. When using robots, the environment includes the robot's own body, its shape and materi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…However, these methods can be seen as deepening rather than narrowing the brain/body distinction: In these approaches, the robot's form is usually a fixed shell, previously designed by human engineers, controlled by the machine learning algorithm. In contrast, there is a small but growing literature on embodying intelligence directly into the body of the robot (Nakajima et al, 2015), and in machine learning methods that evolve robot bodies to enhance this and other forms of intelligence (Powers et al, 2020). A small but growing literature on robots capable of self-modeling also blurs the distinction between embodied robots and non-embodied AI methods.…”
Section: Life Is Embodied: Ais Are Notmentioning
confidence: 99%
“…However, these methods can be seen as deepening rather than narrowing the brain/body distinction: In these approaches, the robot's form is usually a fixed shell, previously designed by human engineers, controlled by the machine learning algorithm. In contrast, there is a small but growing literature on embodying intelligence directly into the body of the robot (Nakajima et al, 2015), and in machine learning methods that evolve robot bodies to enhance this and other forms of intelligence (Powers et al, 2020). A small but growing literature on robots capable of self-modeling also blurs the distinction between embodied robots and non-embodied AI methods.…”
Section: Life Is Embodied: Ais Are Notmentioning
confidence: 99%
“…To the best of our knowledge, the only work that addressed a similar research question are [16][17][18], where the sensory apparatus is evolved in different kinds of hard robots. Another work on this topic is [19], which has shown that sensor placement can alter the landscape of the controller loss function, thus guiding evolution towards better controllers. However, the context of that work was unicycle non-holonomic mobile robots.…”
Section: Introductionmentioning
confidence: 99%
“…To the best of our knowledge, the only works that addressed similar research questions are [19][20][21], although those works focused on evolving the sensory apparatus of hard robots. Another related work is [22], where it has been shown that the landscape of the controller loss function depends on the sensors placement, which in turn conducts evolution towards better controllers. However, the context of that work is unicycle non-holonomic mobile robots.…”
Section: Introductionmentioning
confidence: 99%